Improvement Of Landslide Handling On Filled Land In Cidahu-Cieurih Road, Cidahu District, Kuningan Regency - Yanyan Agustian; Asep Setiawan; Bambang Eko Widyanto (Green Publisher Indonesia, 2024)
This research is based on the issue of soil landslide in the embankment area of Cidahu - Cieurih Road. Geotechnical analysis involves cone penetration testing, boreholes, and laboratory testing to obtain soil property data. The results indicate the presence of soil layers with different characteristics, such as clay, sand, and silty clay. The analysis method utilizes PLAXIS 3D V20 for slope stability modeling. The modeling results show that the existing slope condition is unsafe, and two alternative treatments are proposed. Alternative 1 involves replacing the existing retaining wall with a new one and adding ribs, resulting in an SF of 1.516. Alternative 2 involves using the existing sheet pile with the addition of a retaining wall and embankment, resulting in an SF of 1.63. This research concludes that Alternative 2, utilizing the existing sheet pile and retaining wall, provides better slope stability results with an SF that meets safety standards.